The Perception of Minorities toward the Turkish State: The Case of Ethno-religious Communities - Beylunioglu, Anna Maria; Kaymak, Özgür (Poligrafi, 2021)
The relationship between state and non-Muslim communities has been a delicate issue since the founding of the Turkish Republic despite the principle of secularism stated in its constitution. Against this background, the association of national identity with Sunni-Islam has been the main marker of inclusion/exclusion to the national identity. Especially since 2002 when the Justice and Development Party (JDP) came to power, the debates with regard to freedom of religion and the rights of religious minorities came to fore. Over the course of decades there have been numerous studies approaching the state’s perspective towards religious minorities. However, there are still scarce amount of academic studies that focuses on citizenship experiences of the members of these communities in their daily and social life practices. In this article, we first provide a historical perspective of the state towards religious minorities from the establishment of the Republic until today including the JDP period. In the second part of this study we aim to explore recasting perspectives of the non-Muslim minorities over the previous decade by taking the standpoint of the members of Greek Orthodox, Jews and Armenian communities. To this end, we conduct in-depth interviews with the members of these communities who are residing in Istanbul. Finally, new negotiation fields which have been flourishing among these communities will be addressed.